Modularly Design for Waste Heat Recovery System in Subway Based on Air Source Heat Pump. (2017) - Chai, Yongjin; Sun, Tingting; Han, Haotian; Cao, Feng; Liu, Yanfeng
Abstract: It shows that there's an amount of waste heat in subway spaces, and temperature in subway, especially in tunnel, rises year by year. Excess waste heat is traditionally excluded by ventilation and air conditioning systems causing additional power consumption and thermal pollution to the environment. A new scheme is raised in this study to recover waste heat from air in subway tunnel and simultaneously to provide a by-product of air temperature slashing in tunnel. This waste heat recovery system consists of a few modularized air/water heat pumps and a water loop to deliver heat energy to stakeholders. Corresponding to conditions in tunnel and energy usage, working modes for the system are recommended. Mathematical models for major devices of heat pump, such as compressor, condenser, expansion valve and evaporator, are established. Basing on the models, the devices are modularly designed for subway tunnel conditions specifically. Finally, advantages and disadvantages are discussed.